Arthroscopic Technique for Reduction and Fixation of Adolescent Tibial Eminence Fracture using a Cannulated Screw - Mamdouh E. Masri,; Taha A. Samman,; Ali G. Chaudhary,; Jung Y. Mah,; Rick A. Ogilvie, (Journal of King Abdulaziz University: Medical Sciences, 2023)
This study describes an arthroscopic technique for reduction and fixation of tibial eminence fracture using cannulated screw in six patients aged 12-18 years, with a follow-up after 6-48 months. We used subjective, clinical and radiological outcome measures during the follow-up. On last follow-up, all patients demonstrated full range of motion in the affected knee comparable with the contralateral knee. Our conclusion is that arthroscopic reduction and fixation of adolescent tibial eminence fracture is an acceptable, and safe method of fixation with larger fragments with no concern to growth in this age group of patients.